2015
DOI: 10.1097/prs.0000000000001283
|View full text |Cite
|
Sign up to set email alerts
|

Nipple-Sparing Mastectomy in Patients with Previous Breast Surgery

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…Concerns are mostly related to increased early postoperative complications such as infection, wound healing problems, and ischemia or necrosis of the skin or NAC [18,19,20]. Age, skin incision, flap thickness, reconstruction type, smoking, neoadjuvant chemotherapy, preoperative irradiation, and comorbidities have been reported as risk factors for ischemic complications concerning the skin and NAC [1,2,3,4,18,19,21,22,23,24,25,26]. Patients with an increased BMI and DM are likely to have additional complications due to associated vascular disease [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns are mostly related to increased early postoperative complications such as infection, wound healing problems, and ischemia or necrosis of the skin or NAC [18,19,20]. Age, skin incision, flap thickness, reconstruction type, smoking, neoadjuvant chemotherapy, preoperative irradiation, and comorbidities have been reported as risk factors for ischemic complications concerning the skin and NAC [1,2,3,4,18,19,21,22,23,24,25,26]. Patients with an increased BMI and DM are likely to have additional complications due to associated vascular disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nipple-sparing mastectomy (NSM) has been proven to be an oncologically safe procedure in breast cancer surgery [1,2,3,4]. With primary implant reconstruction, NSM has become the best treatment option for women requiring mastectomy due to better cosmetic result, greater satisfaction, and better quality of life compared to modified radical mastectomy or skin-sparing mastectomy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Frederick et al (17), the IBR rate after mastectomy for ILBLR was 60%. Our rate of 32.8% reflects careful patient selection to achieve a high success rate and reasonably low complication rate.…”
Section: Discussionmentioning
confidence: 93%
“…In our series, nipple-areola-sparing mastectomy followed a quadrantectomy for breast cancer in the vast majority of cases, as expected in a cancer center, and followed aesthetic breast surgery (mastopexy, breast augmentation, or reduction mammaplasty) in only a few patients. In 2015, Frederick et al 15 reported a smaller cohort of patients including 187 nipple-sparing mastectomies in 160 women after previous breast surgery (154 lumpectomies, 27 breast augmentations, and six reduction mammaplasties): no significant differences in total complications, ischemic complications, nipple loss, or implant loss were associated with prior breast surgery compared to a cohort of patients with no previous surgery. However, the article focused on reconstruction and complications, and oncologic outcomes were not reported.…”
Section: Discussionmentioning
confidence: 99%